Nasab Anak Di Luar Perkawinan dalam Penetapan Pengadilan Agama di Indonesia - Husni, Syukriya; Syahriani, Fadilla; Husni, Nidaul; Mulyani, Fini Fajri; Gazali, Gazali (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2024)
In the context of family law, the nasab of children outside of marriage has grown to be a complicated legal and social issue in many nations, including Indonesia. With a particular emphasis on the ruling of the Pengadilan Agama Talu Number 173/Pdt.P/2021/PA.Talu, this article examines the question of the nasab of children born outside of marriage within the context of a Religious Court ruling. In order to determine the nasab of children born outside of marriage, this article employs both national legal requirements and the principles of Islamic law. We also examine the Talu Religious Court's ruling, which is the major point of interest. The analysis covers the legal factors, justifications, and ratio decidendi that the Religious Court used to reach its decision. It is critical to comprehend how the Religious Court developed legal principles, interpreted legal authorities, and considered the decision's social ramifications. The piece also looks at how the Talu Religious Court's ruling may affect family courts and society at large. The paper concludes by summarizing the consequences of the Talu Religious Court's ruling regarding the determination of the nasab of unmarried children and illustrating how legal perspectives have evolved in this area. This article may offer legal professionals, academics, and the general public new perspectives on the problem of the nasab of children born outside of marriage and the function of Religious Courts in governing and adjudicating such matters. In order to safeguard children's rights and preserve a harmony between religious norms and legal requirements in the country, more research in this field is required to determine the long-term effects of such rulings.